Forecasting Volcanic Eruptions - Paone, Angelo; Yun, Sung-Hyo (IntechOpen, 2020)
The chapters presented in this International Volcanological Special Issue consider the characteristic features of a single volcano and/or a number of volcanoes worldwide (Jos and Biu Plateau volcanic provinces, Nigeria; Kachchh Rift Zone, Gujarat, India; Guamsan Caldera, Cheongsong, Korea; Somma-Vesuvius volcano, Napoli, Italy) in terms of future volcanic activity. The technical methods used are wide, innovative, as well as classic and reflect the knowledge presented in each chapter. The last chapter, however, deals with a new conceptual and methodological approach for the evaluation of volcanic risk. All these volcanoes (except Somma-Vesuvius volcano) are poorly studied so they deserve more attention, which is the goal of this volcanological book. Further studies are welcome to deepen the knowledge of each of the volcanoes presented.